2022
DOI: 10.3390/biotech11010001
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Insights into the Composition and Function of Microbes Associated with the Rootzone of Datura inoxia

Abstract: The purpose of this paper is to elucidate the roles that microbes may be playing in the rootzone of the medicinal plant Daturainoxia. We hypothesized that the microbes associated with the Datura rootzone would be significantly different than the similar surrounding fields in composition and function. We also hypothesized that rhizospheric and endophytic microbes would be associated with similar metabolic functions to the plant rootzone they inhabited. The methods employed were microbial barcoding, tests of ess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The authors concluded that the obtained information provides a start for phytopathology studies and the recognition of microorganisms that colonize these exterior parts of plants (Su et al, 2022). Senn et al (2022) analyzed the composition and function of microorganisms associated with the radicular zone of the medicinal plant Datura inoxia, and found that the principal genera associated with the plant's rhizosphere were Flavobacterium, Pedobacter, and Paenibacilus, among others. Bacteria of the genus Flavobacterium are known to possess a tyrosine ammonia-lyase gene, which has been employed to optimize the production of aromatic compounds of pharmaceutical interest.…”
Section: Implications In Ecogenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the obtained information provides a start for phytopathology studies and the recognition of microorganisms that colonize these exterior parts of plants (Su et al, 2022). Senn et al (2022) analyzed the composition and function of microorganisms associated with the radicular zone of the medicinal plant Datura inoxia, and found that the principal genera associated with the plant's rhizosphere were Flavobacterium, Pedobacter, and Paenibacilus, among others. Bacteria of the genus Flavobacterium are known to possess a tyrosine ammonia-lyase gene, which has been employed to optimize the production of aromatic compounds of pharmaceutical interest.…”
Section: Implications In Ecogenomicsmentioning
confidence: 99%
“…Bacteria of the genus Flavobacterium are known to possess a tyrosine ammonia-lyase gene, which has been employed to optimize the production of aromatic compounds of pharmaceutical interest. They also found precursors to vegetal growth with antioxidant and phytoprotective compounds (Senn et al, 2022). On the other hand, a study in 2021 performed a metagenomic analysis of promotor genes involved with vegetal growth and the carbon cycle in the rhizosphere of corn fields with different land use histories.…”
Section: Implications In Ecogenomicsmentioning
confidence: 99%
“…This compound was also shown to have protective effects against b-amyloid induced neurotoxicity in vitro and requires more research in treating Alzheimer's disease. NAChRs are vital targets in the drug discovery field because of their role in several disorders such as Tourette's syndrome, anxiety, depression, smoking cessation, and irritable bowel syndrome (Leonard et al, 2000;Navarro et al, 2000;Tucci et al, 2003;Senn et al, 2022). Ligands of this receptor that specifically bind to nAChR are particularly significant for drug discovery.…”
Section: Effect On Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%
“…In applied soil science, shotgun metagenomics techniques have the benefit of amplifying sequences from throughout the genome, including coding sections, resulting in a high sequencing depth but at a greater cost. 16S Meta barcoding is a diagnostic technique for bacterial and archaeal identification used in clinical sciences and plant ecology (Senn et al 2022). Targeted 16S rRNA amplicons sequenced by a variety of methods are currently being used to examine the microbiota composition in detail.…”
Section: Introductionmentioning
confidence: 99%